Effectiveness of herpes zoster vaccination in an older United Kingdom population. Issue 17 (19th April 2018) - Walker, Jemma L.; Andrews, Nick J.; Amirthalingam, Gayatri; Forbes, Harriet; Langan, Sinead M.; Thomas, Sara L.
Highlights: Live zoster vaccine had good vaccine effectiveness (VE) in UK public health use. VE against incident zoster was 64%, and against post-herpetic neuralgia was 81%. VE was very similar in the two age groups targeted for vaccination. VE was lower (47%) among those with history of zoster. The UK zoster vaccine programme may be more cost-effective than previous estimates. Abstract: Background: Vaccination against herpes zoster was introduced in the United Kingdom in 2013 for individuals aged 70 years, with a phased catch-up campaign for 71–79 year olds. Vaccine introduction has resulted in a marked fall in incident herpes zoster and in post-herpetic neuralgia (PHN), but formal evaluation of vaccine effectiveness is needed. Methods: In a population-based cohort study of older individuals born between 1933 and 1946, we used linked UK anonymised primary care health records for the first three years of the vaccination programme (01/09/2013–31/08/2016) and multivariable Poisson regression to obtain incidence rates and vaccine effectiveness (VE) against zoster and PHN. Results: Among 516, 547 individuals, 21% were vaccinated. Incidence of zoster was 3.15/1000 person-years in vaccinees and 8.80/1000 person-years in unvaccinated individuals. After adjustment, VE was 64% (95%CI = 60–68%) against incident zoster and 81% (95%CI = 61–91%) against PHN, with very similar VE estimates in the routine and catch-up cohorts. VE against zoster was lower in those with a previous history of zoster: 47% (95%CI = 31–58%) versus 64% (95%CI = 60–68%) in those without previous zoster. There was evidence of waning VE over time, from 69% (95%CI = 65–74%) in the first year after vaccination to 45% (95%CI = 29–57%) by the third year. Conclusion: This first formal assessment of VE in the UK zoster vaccination programme demonstrates good effectiveness of zoster vaccine, and very good protection against PHN. The findings provide evidence that VE is similar across the age groups targeted for vaccination in the UK, and on duration of protection of the vaccine in public health use. The study provides key information for decision-makers about the future direction of UK zoster vaccination programme, indicating that the live zoster vaccine may be more cost-effective than estimated previously. It also supports efforts to communicate the benefits of zoster vaccination to address the declining coverage observed across the UK.